Human T cell glycosylation and implications on immune therapy for cancer. Issue 10 (2nd October 2020) - De Bousser, Elien; Meuris, Leander; Callewaert, Nico; Festjens, Nele
ABSTRACT: Glycosylation is an important post-translational modification, giving rise to a diverse and abundant repertoire of glycans on the cell surface, collectively known as the glycome. When focusing on immunity, glycans are indispensable in virtually all signaling and cell-cell interactions. More specifically, glycans have been shown to regulate key pathophysiological steps within T cell biology such as T cell development, thymocyte selection, T cell activity and signaling as well as T cell differentiation and proliferation. They are of major importance in determining the interaction of human T cells with tumor cells. In this review, we will describe the role of glycosylation of human T cells in more depth, elaborate on the importance of glycosylation in the interaction of human T cells with tumor cells and discuss the potential of cancer immunotherapies that are based on manipulating the glycome functions at the tumor immune interface. 1, 2